Periodontal regeneration: is it still a goal in clinical periodontology? - Cirelli, Joni Augusto [UNESP]; Fiorini, Tiago; Moreira, Carlos Heitor Cunha; de Molon, Rafael Scaf [UNESP]; Dutra, Tamires Pereira; Sallum, Enílson Antonio (FapUNIFESP (SciELO), 2021)
In the last decades, Periodontal Regeneration has been one of the most discussed topics in Periodontics, attracting the attention of researchers and clinicians. This can be justified by the evident and continuous progress observed in the field, characterized by a better understanding of the biological mechanisms involved, significant improvement of operative and technical principles, and the emergence of a wide range of biomaterials available for this purpose. Together, these aspects put the theme much in evidence in the search for functional and esthetic therapeutic solutions for periodontal tissue destruction. Despite the evident evolution, periodontal regeneration may be challenging and require the clinician to carefully evaluate each case before making a therapeutic decision. With a critical reassessment of the clinical and preclinical literature, the present study aimed to discuss the topic to answer whether Periodontal Regeneration is still a goal in clinical periodontology. The main aspects involved in the probability of success or failure of regenerative approaches were considered. A greater focus was given to intrabony and furcation defects, clinical conditions with greater therapeutic predictability. Aspects such as more appropriate materials/approaches, long-term benefits and their justification for a higher initial cost were discussed for each condition. In general, deep intrabony defects associated with residual pockets and buccal/lingual class II furcation lesions have predictable and clinically relevant results. Careful selection of the case (based on patient and defect characteristics) and excellent maintenance are essential conditions to ensure initial and long-term success.
Keywords: Bone and Bones; Furcation Defects; Periodontal Diseases; Periodontics; Regeneration